Improving Cognitive Functioning through Nutritional Intervention Program: A study on School going Children - Arya, Bhavana; Arya, Bhavana; Rathore, Suyesha Singh; Sharma, Mridula (International Journal of Psychosocial Rehabilitation, 2020)
Food is an integral part of our lifestyle and it has been realized that food affects all aspects of our being. It has also been a topic of research that food affects our cognitive functioning. The current study aimed to recognize nutritional deficiencies in children from the age 8-11 years. 141 children deficient in vitamin B12, iron, folic acid and vitamin D were identified on the basis of a blood test and were included in the study. Baseline measures of cognitive functioning were established on Malin’s Intelligence Scale for Indian Children (MISIC; Malin, 1969). Random assignment of 91 subjects was done to the experimental group and the remaining 50 subjects were observed as controls. The experimental group was given an intervention plan which consisted of a diet plan under the guidance of a nutritionist, micro-nutrient supplements under the guidance of a paediatrician and awareness regarding healthy food habits by the researcher. After 45 days of intervention post test scores were obtained. There was a significant improvement in the cognitive functioning of children in the experimental group. The post test scores of the experimental group were also significantly higher than the post test scores of the control group. The findings of the study confirmed the role of nutrition in the cognitive development of children.